2021
DOI: 10.1108/hff-10-2020-0668
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic mixed bioconvection of oxytactic microorganisms in a nanofluid-saturated porous cavity heated with a bell-shaped curved bottom

Abstract: Purpose This study aims to investigate thermo-bioconvection of oxytactic microorganisms occurring in a nanofluid-saturated porous lid-driven cavity in the presence of the magnetic field. The heating is provided through a bell-shaped curved bottom wall heated isothermally. The effects of the peak height of the curved bottom wall, bioconvection Rayleigh number (Rb), Darcy number (Da), Hartmann number (Ha), Peclet number (Pe), Lewis number (Le) and Grashof number (Gr) on the flow structure, temperature and the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The Hall effect and Joule heating are also supposed to be insignificant (Maxwell, 1904) along with the negligible contributions of viscous dissipation and radiation effects (Nield and Bejan, 2013; Manna et al , 2021b). With the aforesaid assumptions, the dimensional and dimensionless transport equations are derived (Massoudi et al , 2020; Biswas et al , 2021f; Sarkar, 2021; Al-Farhany, 2021b; Biswas et al , 2021c) and given below.…”
Section: Methodology and Mathematical Modelingmentioning
confidence: 99%
“…The Hall effect and Joule heating are also supposed to be insignificant (Maxwell, 1904) along with the negligible contributions of viscous dissipation and radiation effects (Nield and Bejan, 2013; Manna et al , 2021b). With the aforesaid assumptions, the dimensional and dimensionless transport equations are derived (Massoudi et al , 2020; Biswas et al , 2021f; Sarkar, 2021; Al-Farhany, 2021b; Biswas et al , 2021c) and given below.…”
Section: Methodology and Mathematical Modelingmentioning
confidence: 99%
“…Jamuna and Balla (2021) deliberated the influence of heat absorption/generation, thermophoresis and Brownian motion on isotherms, isoconcentrations of microorganisms and flow line fields of Buongiorno's type nanofluid within a square porous cavity. Biswas et al (2021) perceived marginal augmentation in the nondimensional rate of heat transport with growing values HFF 33,12 of magnetic field parameter in their work on nanofluid isotherms and isoconcentrations of microorganism characteristics inside a closed cavity pondered with gyrotactic microorganisms. Recently, many authors (Shekar and Kishan, 2015;Chamkha et al, 2018;Dogonchi et al, 2019;Tayebi and Chamkha, 2020;Seyyedi et al, 2020;Tayebi et al, 2021aTayebi et al, , 2021bTayebi et al, , 2021cKrishna et al, 2021;Zidan et al, 2022;Nayak et al, 2022;Tayebi et al, 2022;Tayebi et al, 2023;Meenakshi et al, 2023;Balla et al, 2023) have presented mass and heat transport of various nanoliquids over dissimilar geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In the background of relatively few pioneering works (Incropera, 1988; Biswas et al , 2015; Biswas et al , 2017; Das and Basak, 2017; Lukose and Basak, 2021; Hamzah et al , 2021), most of the studies address complex phenomena (Biswas et al , 2016a; Jalili et al , 2019; Sarkar et al , 2021; Mondal et al , 2022) involving multiple physics like buoyancy, nanofluid (Rahimi et al , 2019; Ghalambaz et al , 2020; Dutta et al , 2021; Dogonchi et al , 2018; Jalili et al , 2022a), hybrid nanofluid (Sarkar et al , 2015; Ghalambaz et al , 2019; Ali, 2020; Biswas et al , 2021a, 2021b; Manna and Biswas, 2021; Jalili et al , 2022b), magnetic field (Kabeel et al , 2015; Manna et al , 2021a; Giwa et al , 2021; Jalili et al , 2021; Jalili et al , 2022d), porous medium (Comini et al , 1974; Bejan et al , 2004; Biswas et al , 2017; Debayan and Basak, 2017; Manna et al , 2021b; Jalili et al , 2022c), microorganisms (Biswas et al , 2021c, 2021d, 2021e), etc. The studies are found to exist in simple (Lewis, 1987; Biswas et al , 2016a; Manna et al , 2019) to complex geometries (Mandal et al , 2022; Saha et al , 2022a, 2022b; Hussain and Oztop, 2021; Biswas et al , 2021d; Al-Farhany et al , 2021; Bhatti et al , 2021) without or with embedded obstructions (Biswas et al , 2021e; Das, and Basak, 2017; Hussain and Oztop, 2021; Mallick et al , 2021; Sivaraja and Sheremet, 2017).…”
Section: Introductionmentioning
confidence: 99%